Affective Meaning in Bruno Mars Song Lyrics - putri millenia salsabila (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
This study focuses on positive and negative affective meaning in Bruno Marsâ€™s song lyrics. The study aims to analyze â€œBruno Mars song lyricsâ€ in terms of semantic studies, especially affective meaning. The objective of this research is to find out how affective meaning is used in Bruno Marsâ€™s song lyrics viewed in term of Leechâ€™s theory. Source data from album Doo-Wops & Hooligans (2010). This study used descriptive qualitative method. Data collection is done by searching and downloading, reading song lyrics, identifying and selecting the song lyrics, and coding the lyrics. Based on the analysis, researcher found affective meaning such as angry, sad, disappointed, confused and happy. The most dominant implication in the object of song lyrics is negative affective meaning. The use of affective meaning depends on the context of the situation that occurs when the utterance is spoken. Affective meaning can be interpreted as meaning that arises because of the use of certain words or sentences and expressions.